Making occupational health and safety training relevant for farmers: Evaluation of an introductory course in occupational health and safety in Norway. (November 2018) - Holte, Kari Anne; Follo, Gro
Highlights: Uptake of OHS interventions are influenced by many contextual factors and mechanisms. Contextual factors and mechanisms may change throughout the intervention process. OHS training considering OHS should be embedded in farmers practical reality. Focusing on the responsibility for others improves safety within agriculture. Abstract: Agriculture is a hazardous industry, with a high frequency of injuries. As agriculture is an industry mostly consisting of small enterprises, it may be difficult to prevent injuries. In Norway, an OHS course is available for farmers. This study aims to evaluate this course. The evaluation is a prospective exploratory case study evaluation using qualitative interviews. The results suggest that there was not an increase in use and understanding of OHS systems, despite being the aim of the course. The farmers easily absorbed the practical part of the course, getting solutions and ideas for practical risk prevention at own farm. However, using systems adjusted to farm characteristics required external, face-to-face practical involvement at the farm. The study revealed that the course design was not optimal for farmers, as it addressed the farmers as managers, requiring an understanding of theory, while farmers mainly understand their occupation as practical. The course design should be reconsidered to integrate farmers' daily practices.